Fodder trees and shrubs in the Ethiopian highlands: Service and product functions - Mekonnen, Kindu; Bezabih, Melkamu; Assefa, Getnet; Adie, Aberra; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Media Training Workshop on Climate Smart Livestock Feed and Forage Innovations. Addis Ababa, Ethiopia.